2016
DOI: 10.1371/journal.pone.0157070
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of a Novel Family of Cyclophilins, the AquaCyps

Abstract: Cyclophilins are ubiquitous cis-trans-prolyl isomerases (PPIases) found in all kingdoms of life. Here, we identify a novel family of cyclophilins, termed AquaCyps, which specifically occurs in marine Alphaproteobacteria, but not in related terrestric species. In addition to a canonical PPIase domain, AquaCyps contain large extensions and insertions. The crystal structures of two representatives from Hirschia baltica, AquaCyp293 and AquaCyp300, reveal the formation of a compact domain, the NIC domain, by the N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Considering Cyps from other organisms, variability in kinetic parameters was observed for the two TgCyps. Indeed, the catalytic efficiency of TgCyp23 for the AAPF peptide substrate was high ( k cat / K m = 2.89 × 10 6 M –1 s –1 ) and resembled that of human CypA and some other Cyps, implying that TgCyp23 is a highly active PPIase. On the contrary, TgCyp18.4 is also active as a PPIase but differs significantly from TgCyp23 and human CypA.…”
Section: Resultsmentioning
confidence: 96%
“…Considering Cyps from other organisms, variability in kinetic parameters was observed for the two TgCyps. Indeed, the catalytic efficiency of TgCyp23 for the AAPF peptide substrate was high ( k cat / K m = 2.89 × 10 6 M –1 s –1 ) and resembled that of human CypA and some other Cyps, implying that TgCyp23 is a highly active PPIase. On the contrary, TgCyp18.4 is also active as a PPIase but differs significantly from TgCyp23 and human CypA.…”
Section: Resultsmentioning
confidence: 96%
“…Since it was reported that PPIases can form homo-oligomers ( Budiman et al, 2009 ; Zhang et al, 2011 ; Jakob et al, 2016 ; Polley et al, 2016 ) we studied the possibility that CypA and CypB were able to oligomerize. As shown in Figure 7A , when we subjected CypA or CypB to SDS-PAGE and Western blot analysis, a single protein band corresponding to the recombinant CypA or CypB was detected as expected for the monomeric form of these cyclophilins.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PPIases can form homo-oligomers ( Zhang et al, 2011 ; Jakob et al, 2016 ; Polley et al, 2016 ) although, in the family of cyclophilins, only a few cases have been reported: the human hCypA ( Zhang et al, 2011 ) and the Trichomonas vaginalis cyclophilin 1 ( Martin et al, 2018 ). In addition, in the case of dimeric PPIases, no homodimer formation has been reported dependent on disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation of organic matter and hydrocarbons [49] Denitrification [50] Secretion of extracellular proteins and biofilm formation [51] Caulobacteraceae Caulobacter Secretion of extracellular polymers [50] Adapts to and may be able to degrade triclosan (TCS) […”
Section: Family Genus Environmental Functionsmentioning
confidence: 99%